Species composition and distribution characteristic of seaweeds on seagrass beds in Phu Quoc island - Hieu, Nguyen Trung; Ben, Hoang Xuan; Dat, Mai Xuan (Vietnam Journal of Marine Science and Technology, 2019)
Seagrass beds in Phu Quoc are a favorable environment for seaweed development (bottom-living and epiphytic species). The surveys at 18 sites along the coastal line in Phu Quoc island showed that 69 species belonging to 4 phyla of seaweed were recorded on seagrass beds in Phu Quoc island. Among them, there are 27 species of Rhodophytes (comprising 37% of total species), 19 Chlorophytes (28%), 16 Ochrophytes (24%) and 7 Cyanobacteriophytes (11%). We identified 12 species of epiphytic algae including three species on seagrass and nine species on both seagrass and the substratum. The characteristics of substratum may play an important role for diversity and distribution of the bottom-living seaweed. For epiphytic algae on bigger size seagrass, the diversity of epiphytic species on the top of seagrass leaf is higher than on the root and other parts of leaf.